Neue Informations- und Kommunikationstechnik: Lösung für den Arbeitsmarkt der Zukunft? - Stefan Klein; Irene Bertschek; Oliver Falck; Constantin Mang (Wirtschaftsdienst, 2012)
Moderne Kommunikationsmittel haben Arbeitsprozesse tiefgreifend verändert, Qualifikationsanforderungen nachhaltig verschoben und neue Beschäftigungsformen gefördert. Die Funktionsmechanismen des Arbeitsmarktes, aber auch die Jobsuche, wurden durch sie transparenter und effizienter. Die Internetökonomie begründet eine ganz neue Generation von technischen Möglichkeiten, deren Ausgestaltung bestimmt, wie groß ihr Beitrag für innovative Lösungen am Arbeitsmarkt sein kann. Dies diskutierten die Autoren im Rahmen einer Panelsitzung, die der Wirtschaftsdienst auf der Jahrestagung des Vereins für Socialpolitik 2012 organisiert hat. – – Recent technological advances have prompted both utopian and dystopian visions of the transformation of work. The design of humane work environments requires not only a thorough understanding of technological affordances but also - critically - of work practices and their development. Many workers use advanced communication technologies on the job. It is assumed that this may foster economic productivity and growth, but there may also be negative effects, i.e. problems due to information overflow, diversion of attention and blurred boundaries between professional life and family life. The Internet has become one of the most popular tools for job seekers and changed the way workers and firms are matched on the job market. There is evidence that job changers who found their new job through the Internet are better matched than those who found a new job through newspapers, friends or other channels. The Internet has the potential to improve the matching quality of the labour market.
Keywords: E31; E42; E50; 330; Arbeitswelt; Sozialer Wandel; Innovation; Produktivität; Virtuelle Gemeinschaft; Arbeitsmarkt